FINANCIAL DISCIPLINE AND THE POSSIBILITY OF ACHIEVING ECONOMIC STABILITY IN IRAQ (2004-2019) - Ruaa Naseer Kadhim; Sarah Abdul-Razzaq Hasan Al-Harkani (Scholar Express Journals, 2023)
Financial discipline is the method that used to manage public money in a way that shows the desire to comply with financial rules. It explains how to manage public finances that aligns current spending with planned spending in order to achieve long term financial aims. It embodies an important part of the process of monitoring the public budget and ensuring implementing it on time with the aim of directing government financial operations. This works to achieve stability in the levels of economic activity. Some economists believe that linking economic activity to price fluctuations requires monetary policy to conduct a moderate increase in prices in the event of an expansion in economic activity, which contributes to increasing levels of profitability and raising optimistic expectations that accelerate and stimulate economic action. Monetary stability is a fundamental goal that the monetary authorities seek to achieve in order to link the monetary balance and achieve stability in the rest of the economic variables
Keywords: Financial discipline; possibility; economic stability